Glial fibrillary acidic protein (GFAP): modulation by growth factors and its implication in astrocyte differentiation - F.C.A. Gomes; D. Paulin; V. Moura Neto (Brazilian Journal of Medical and Biological Research, 1999)
Intermediate filament (IF) proteins constitute an extremely large multigene family of developmentally and tissue-regulated cytoskeleton proteins abundant in most vertebrate cell types. Astrocyte precursors of the CNS usually express vimentin as the major IF. Astrocyte maturation is followed by a switch between vimentin and glial fibrillary acidic protein (GFAP) expression, with the latter being recognized as an astrocyte maturation marker. Levels of GFAP are regulated under developmental and pathological conditions. Upregulation of GFAP expression is one of the main characteristics of the astrocytic reaction commonly observed after CNS lesion. In this way, studies on GFAP regulation have been shown to be useful to understand not only brain physiology but also neurological disease. Modulators of GFAP expression include several hormones such as thyroid hormone, glucocorticoids and several growth factors such as FGF, CNTF and TGFß, among others. Studies of the GFAP gene have already identified several putative growth factor binding domains in its promoter region. Data obtained from transgenic and knockout mice have provided new insights into IF protein functions. This review highlights the most recent studies on the regulation of IF function by growth factors and hormones.